2021
DOI: 10.1038/s41598-021-91202-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of carbapenemase producing enterobacteria using an ion sensitive field effect transistor sensor

Abstract: The timely and accurate detection of carbapenemase-producing Enterobacterales (CPE) is imperative to manage this worldwide problem in an effective fashion. Herein we addressed the question of whether the protons produced during imipenem hydrolysis could be detected using an ion sensitive field effect transistor (ISFET). Application of the methodology on enzyme preparations showed that the sensor is able to detect carbapenemases of the NDM, IMP, KPC and NMC-A types at low nanomolar concentrations while VIM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The results showed that without zinc supplementation, the color development could be inhibited by EDTA in the majority of the MβL producing strains (Figure 4A, left panel). However P. mirabilis EUG91, that produces low quantities of VIM-1 (10), failed to give a positive reaction even after six hours of incubation. Thus, EDTA inhibition could be used for the identification of MβL producers with the above method when bacteria are cultured without excess zinc but this would reduce the sensitivity for some strains exhibiting low levels of functional periplasmic MβLs.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The results showed that without zinc supplementation, the color development could be inhibited by EDTA in the majority of the MβL producing strains (Figure 4A, left panel). However P. mirabilis EUG91, that produces low quantities of VIM-1 (10), failed to give a positive reaction even after six hours of incubation. Thus, EDTA inhibition could be used for the identification of MβL producers with the above method when bacteria are cultured without excess zinc but this would reduce the sensitivity for some strains exhibiting low levels of functional periplasmic MβLs.…”
Section: Resultsmentioning
confidence: 96%
“…In pZE21 clones transcription of the cloned β-lactamase gene was induced by 200 ng/ml anhydrotetracycline while in the remaining plasmids expression was constitutive driven by natural promoters of the genes. Proteins were released through sonication (10) in 50 mM sodium phosphate bufffer pH 7 with the exception of the MβL preparations where a 50 mM HEPES, 50 μΜ ZnSO 4 pH 7.2 buffer was used. Hydrolysis of imipenem (NDM-1, NMC-A and OXA-48), cephalothin (CMY-2) or cefotaxime (CTX-M-15) was measured by UV spectrophotometry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A , left). However, P. mirabilis EUG91, which produces low quantities of VIM-1 ( 10 ), failed to give a positive reaction even after 6 h of incubation. Thus, EDTA inhibition could be used for the identification of MBL producers with the above method when bacteria are cultured without excess zinc, but this would reduce the sensitivity for some strains exhibiting low levels of functional periplasmic MBLs.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, during the development of a technique that detects the imipenem acidic hydrolysis product using an ion-sensitive field effect transistor ( 10 ), we observed that reaction mixtures containing CPE yielded a yellowish color that gradually became more intense—something that did not occur for the carbapenemase-negative strains even after prolonged incubation. This phenomenon most likely resulted from the pH drop during imipenem hydrolysis and was due to the complex oligomerization reactions taking place in dense solutions of the compound under acidic conditions yielding chromophoric diketopiperazines ( 11 ).…”
Section: Introductionmentioning
confidence: 99%